LOYALTY AS REFLECTED IN KOYOHARU GOTŌGE’S KIMETSU NO YAIBA COMIC - Gidion Kolondam; Rianna R. J. Sumampouw; Diane M. Tengker (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This research aims to describe the meaning, causes, and impacts of loyalty in Koyoharu Gotoge's Kimetsu No Yaiba comic. This type of research uses descriptive-qualitative research, with data collection techniques using note-taking techniques and data analysis techniques using objective literary theory. Based on the findings of the study, it was found that the meaning of loyalty in Kimetsu No Yaiba comics consists of 3 meanings: obedience, obedience, and determination. In Kimetsu No Yaiba comics there are 8 factors that become causes, namely admiration, anticipation, trust, happiness, love, hatred, optimism, terror, and submission. In addition to the factors that cause loyalty, there are also 4 impacts arising from loyalty: positive impacts on the subject, negative impacts on the subject, positive impacts on the object, and negative impacts on the object.